HUBUNGAN ANTARA KETIDAKPUASAN BENTUK TUBUH DENGAN KEPERCAYAAN DIRI REMAJA PADA KORBAN BODY SHAMING DI SMK AL-GINA - Amalia, Winda; Vebrian, Garry (Nusantara Hasana Journal, 2022)
The body dissatisfaction can  be interpreted as the perspective of someone who believes that their appearance doesn’t meet the criteria of personal standards, which is caused by a negative perceptions. It could a factor an individual feeling not convidence. Self-confidence is a good attitude because it is supported by a sense of confidence, so that someone who has confidence can face a problem without being afraid to make mistakes. The purpose of this study was to determine the relationship between body dissatisfaction with adolescent self-confidence in victim at Al-Gina Vocational School in 2021. This type of research used quantitative methods with a cross sectional approach, the sample in this study is class XII, totaling 119 respondents and using simple random sampling technique. The measuring instrument used is a questionnaire. The data analysis techniques used were univariate, bivariate, chi-square, and correlation test. The result of the research known as the chi-square test obtained p-value 0.000 £ 0.05, which means there is a relationship of between body dissatisfaction with adolescent self-confidence in victim of body shaming at  Al-Gina Vocational School in 2021. The Conclution is that there is a relationship between body dissatisfaction and adolescent self-confidence in victim of body shaming.